2019
DOI: 10.1192/bjb.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Lean management in a liaison psychiatry department: implementation, benefits and pitfalls

Abstract: Aims and methodTo apply process mapping, a component of lean management, to a liaison psychiatry service of an emergency department. Lean management is a strategy that has been adapted to healthcare from business and production industries and aims to improve efficiency of a process. The process consisted of four stages: individual interviews with stakeholders, generation of process maps, allocation of goals and assessment of outcomes.ResultsThere was a significant reduction in length of stay of psychiatric pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…Interventions pilot test Carney et al (2020) Standard creation (Allaudeen et al, 2017;Ben-Tovim et al, 2008;Dickson et al, 2009a;Eller, 2009;Furterer, 2018;Improta et al, 2018;Kane et al, 2015;Mazzocato et al, 2012;Naik et al, 2012;Ng et al, 2010;S anchez et al, 2018;Sanders and Karr, 2015;Vashi et al, 2019;Wolak et al, 2020) Standard maintenance (Allaudeen et al, 2017;Ben-Tovim et al, 2008;Kane et al, 2015;S anchez et al, 2018;Sanders and Karr, 2015;Vashi et al, 2019) Target monitoring (Alexander et al, 2020;Allaudeen et al, 2017;…”
Section: Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions pilot test Carney et al (2020) Standard creation (Allaudeen et al, 2017;Ben-Tovim et al, 2008;Dickson et al, 2009a;Eller, 2009;Furterer, 2018;Improta et al, 2018;Kane et al, 2015;Mazzocato et al, 2012;Naik et al, 2012;Ng et al, 2010;S anchez et al, 2018;Sanders and Karr, 2015;Vashi et al, 2019;Wolak et al, 2020) Standard maintenance (Allaudeen et al, 2017;Ben-Tovim et al, 2008;Kane et al, 2015;S anchez et al, 2018;Sanders and Karr, 2015;Vashi et al, 2019) Target monitoring (Alexander et al, 2020;Allaudeen et al, 2017;…”
Section: Controlmentioning
confidence: 99%
“…Data mining, process steps measurement (Bal et al, 2017;Carter et al, 2012;Dickson et al, 2009a, b;Elamir, 2018;Furterer, 2018;Improta et al, 2018;Matt et al, 2018;Mazzocato et al, 2012;Ng et al, 2010;Nicholas, 2012;S anchez et al, 2018;Sanders and Karr, 2015;White et al, 2014;Wolak et al, 2020) Identification of wastes and root causes (Al Owad et al, 2018;Alowad et al, 2021;Alexander et al, 2020;Allaudeen et al, 2017;Arbune et al, 2017;Bal et al, 2017;Carney et al, 2020;Carter et al, 2012;Chiarini, 2013;Cookson et al, 2011;…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…85% of the studies stated that data and information had been gathered to inform the PM exercise as a substitute for (55%), or in addition to (30%), the group knowledge generated in the facilitated process mapping sessions. This included evidence-based best practice recommendations [35][36][37], interviews [65][66][67][68][69][70], and more detailed approaches such as observations, operational data collection, time-andmotion studies, and video footage. [64,[71][72][73][74] Phase 3 81% of studies included perspectives from diverse stakeholders.…”
Section: Phasementioning
confidence: 99%
“…[74,86,114] Reviewed studies also show that the capacity of PM to facilitate the dialogue between diverse stakeholders helps to smooth barriers and tensions occurring during improvement projects or reach consensus on solutions. [65,74,80,86,97,98,[117][118][119] For example, some studies reported how PM helped to promote the integration of health services across different settings by developing clinical evidence-based recommendations agreed among different healthcare professionals. [66,79,81,83] Finally, studies describe how PM can be a valuable tool for documenting a care process for further dissemination.…”
Section: Bene Ts Of Using Pm In Improvement Workmentioning
confidence: 99%